Society’s Willingness to Pay for Certified Dry Firewood Energy in Chile - García, Leidy Y.; Cerda, Arcadio A.; Lagos, Rocio del P.; Muñoz, Patricio I.; Muñoz, Monserrat (Frontiers in Energy Research, 2021)
Introduction: Air pollution is present in most cities in Chile due to smoke produced from firewood, as happened in many developing countries, generating various health problems among the population. This situation is especially prevalent in all cities in central and southern Chile. To mitigate it, the government implemented several measures, among which are the promotion of the use of certified dry firewood and hourly restrictions on the use of wood-burning stoves for heating according to the peak emissions of particulate matter. Objective: The objective of this study was to determine the willingness to pay for certified dry firewood as a means of reducing environmental restrictions on the use of wood-burning stoves to heat households. Materials and methods: The study used a non-market valuation, specifically contingent valuation, method using a double-bounded dichotomous choice format with the estimation of biprobit econometric models. Results: The results showed that the average individual was willing to pay 12 USD, and extrapolating that to the local population’s willingness to pay yielded an economic value of 3,415,140 USD, which to a certain extent represents the valuation of air pollution damage. Conclusions: Our results showed that people positively valued the use of dry firewood as a payment vehicle to improve air quality and thereby reduce restrictions on the use of certified dry firewood for heating. Therefore, complementary environmental policy measures should be continued to address the problem of air pollution in both the short and long term.